A study of Vitamin D and parathyroid hormone levels in patients with prostatic cancer - Md. Nasim Akhtar; Kayyum Khan; Shahnawaz Alam; Mohit Mishra; Sachin Rathod; Waqas Alauddin (Asian Journal of Medical Sciences, 2024)
Background: Vitamin D, a key nutrient in the body, has been linked to a decrease in prostate cancer (PCa) morbidity and mortality rates. The study concluded that any compensation mechanism may no longer be adequate for patients with PCa, and further research is needed to understand the mechanisms underlying the relationship between serum Vitamin D and parathyroid hormone (PTH) homeostasis. The findings will help determine cancer prevalence and trends in India and support public health initiatives to control cancer. Aims and Objectives: The aim is to assess the mean values of Vitamin D and PTH in patients with PCa and also to compare these levels with that of healthy controls (non-PCa). Materials and Methods: One hundred participants in the outpatient department of the Department of Biochemistry were assigned as control subjects, and another 100 participants were participants with PCa. 5 mL of fasting venous blood were drawn into red top vials using a disposable syringe and needle in an aseptic manner. PTH and serum Vitamin D were estimated. Results: When comparing PCa patients to healthy controls, the observed Vitamin D level was significantly lower in the former group. Furthermore, a notable distinction in Vitamin D levels was noted between the two groups. Furthermore, we found that PCa patients had higher PTH values than healthy controls. When we compared the PTH values of the two groups, we found a substantial difference. Conclusion: The authors conclude from the study that with alterations in the study parameters in patients with PCa, any compensation mechanism may become insufficient.